Determination of the Ca/P ratio in calcium phosphates during the precipitation of hydroxyapatite using X-ray diffractometry - Zoltan Z. Zyman (Processing and Application of Ceramics, 2013)
The applicability of the X-ray powder diffraction method to the determination of phase composition and Ca/P ratio in precipitates during the nitrous wet synthesis of hydroxyapatite (HA) has been shown. The plotted dependences of the phase composition and the Ca/P ratio on the synthesis time can be used as initial data for the development of new and simple processing routes of calcium phosphate ceramics based on HA of any desired composition.